Urban mobility at the heart of tourist attractiveness, the example of a route in Annaba - HACINI, Nacima (Journal of Human Sciences, 2021)
Annaba is an Algerian city which offers a fairly rich and diversified tourist potential: heritage, landscape, sea are united there. The space that inspires walk or strolling is that of Rizi Amor "Chapui" Boulevard, a continuation of the Coral Bay axis, a space coveted by walkers especially in summer. This space, more accessible to cars than to pedestrians, is of a tourist nature since it runs along the sea offering a beautiful landscape. Summer visitors benefit from the sea and a pedestrian network along a road congested by cars where the walker mutually breathes fresh air and polluted air. In this intervention we will try to focus on a space with tourist assets, which is however invaded by automobile congestion, a polluted environment where it is necessary to reconcile tourism and mobility with a view to sustainable development.